2012
DOI: 10.1371/journal.pone.0029993
|View full text |Cite
|
Sign up to set email alerts
|

Sharpin Contributes to TNFα Dependent NFκB Activation and Anti-Apoptotic Signalling in Hepatocytes

Abstract: TNFα stimulates both pro- and anti-apoptotic signalling in hepatocytes. Anti-apoptotic signalling depends on a cascade of ubiquitylation steps leading to NFκB activation. Using Sharpin-deficient mice, we show that the ubiquitin binding protein Sharpin interacts with Hoip, an E3 ligase which generates linear ubiquitin chains. Sharpin-deficiency sensitized hepatocytes to induction of apoptosis by TNFα even in the absence of transcriptional inhibition. TNFα induced activation of NFκB was strongly reduced in hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 24 publications
0
25
1
1
Order By: Relevance
“…In this study, we only observed a nonsignificant delay of I-kB phosphorylation in Cpdm cultures (Fig. 4E), in contrast to what has been reported for other cell types from Cpdm mice by us (16) and by others (10)(11)(12).…”
Section: Primary Calvarial Cells From Cpdm Mice Display Impaired Ostecontrasting
confidence: 93%
See 3 more Smart Citations
“…In this study, we only observed a nonsignificant delay of I-kB phosphorylation in Cpdm cultures (Fig. 4E), in contrast to what has been reported for other cell types from Cpdm mice by us (16) and by others (10)(11)(12).…”
Section: Primary Calvarial Cells From Cpdm Mice Display Impaired Ostecontrasting
confidence: 93%
“…Having established that impaired osteoblast differentiation is causative for the osteopenia of Cpdm mice, we finally addressed the question of whether TNF signaling is impaired in mesenchymal osteoprogenitor cells from Cpdm mice. We first monitored TNF-a-induced I-kB phosphorylation in primary calvarial osteoblasts and found, in contrast to our previous analysis in primary hepatocytes (16), that there was no significant difference between WT and Cpdm cultures. We also analyzed the possibility that TNF-a treatment would induce apoptosis specifically in Cpdm osteoblast cultures, similar to what has been reported for other cell types (10)(11)(12)16).…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…The NZF domain of SHARPIN seems to be indispensable for NF-κB activation, but not for linear ubiquitination [5] . SHARPIN may also contribute to the anti-apoptotic signaling induced by TNF-α, either through a NF-kB-dependent [14] or -independent pathway [10] .…”
Section: Research Highlightmentioning
confidence: 99%